KINETIKA DEHIDRASI MINYAK JARAK DENGAN KATALIS CAMPURAN NATRIUM BISULFAT DAN ATAPULGIT - Prayoga Suryadarma, Irawadi Jamaran dan M. Ghozin Ghazali (Department of Agroindustrial Technology, Bogor Agricultural University, 2004)
ABSTRACTCastor oil may be dehydrated in such a way that the hydroxyl group, along with a neighboring hydrogen atom, is eliminated, leaving two double bonds. This new form known as dehydrated castor oil (DCO). In the manufacture of DCO, castor oil is subjected to catalytic dehydration. The choice of catalyst is very important in the catalytic dehydration process because the reaction and quality of the resulting product mainly depend on the catalyst. Sodium bisulfate and attapulgite (aluminum-magnesium-silicate) potential to be utilized as catalyst for dehydration of castor oil. The dehydration reaction kinetics of castor oil was investigated with sodium bisulfate–attapulgite mixture as catalyst. The rate of dehydration of castor oil was constructed from experimental data by considering the disappearance of hydroxyl groups. Reactions were carried out at 190, 200, and 210C, and kinetic model was determined for each case. The equilibrium conditions were investigated based on the decreasing of hydroxyl value during the dehydration process for each temperature. In the equilibrium conditions, hydroxyl value of 80.85, 70.81, and 51.59 were reached 150 minutes at 190 and 200C, and 120 minutes at 210C, respectively. The integral method was used to correlate the experimental data. The second order rate equation showed the best fit to the experimental data for all reaction temperature. The rate constant dehydration of castor oil at 190, 200, and 210C are 4,03 x 10-5 [(w%)-1(min)-1], 4,83 x 10-5 [(w%)-1(min)-1], 10,3 x 10-5 [(w%)-1(min)-1], respectively. The activation energy at that condition is 5,24 kcal/mole. Key words : Castor oil, dehydrated castor oil, kinetics